Respostas

2014-03-03T20:51:53-03:00
2x -1      3x-2          x²-2                  sublinhar = cortar
--------- - ----------- = ----------
   3              2            6

2(2x-1) - 3(3x-2)            x²-2
--------------------------- = ----------------------
                 6                        6

4x - 2 - 9x +6 =x² -2
-5x + 4=x² -2
0= x² +5x -4 -2
0= x² +5x -6
       -6                1
--------------- + ----------------- =  -5
         -6                  1
--------------- × ------------------ = -6
x=-6 e x=1